Analyzing Students' Toefl Test Of English Education Deparment Of STKIP Muhammadiyah Enrekang - Umiyati jabri (Edumaspul: Jurnal Pendidikan, 2019)
This study aims to show students’ TOEFL score, sixth and eight semester of English Education Department at STKIP Muhammadiyah Enrekang. The research used descriptive design by quantitative approach. The sample is 40 students of English Education department. The research instrument used TOEFL like test. Descriptive statistics showed the data analysis technique, mean and percentage. . For this study , students got problems in acquiring a TOEFL score with an average score 365 which was still at the basic proficiency category (elementary). From the data analyzing, the researcher found that the highest problem faced by the studentsis is listening section where students got correct answers only 27%. The students got the lowest score is in the short dialogue with the percentage 35%. Then the structure and written expression, students got average score lowest in the aspect of structure (completion) with a percentage 34%. From all parts of the TOEFL test, none of the students got average score more than 50%.